Immigrants’ acquisition of national citizenship in Portugal and Spain: the role of multiculturalism? - Carvalho, J. (2020)
Against the backdrop of a restrictive backlash in Europe, this article examines Portugal and Spain’s policies on immigrants’ acquisition of their national citizenships and assesses their potential convergence towards a common model. Drawing on a qualitative comparative analysis, this investigation also seeks to understand the evolution of the two Iberian countries’ approaches by exploring the dominant theories on the variation of citizenship regimes. A significant degree of policy convergence over an assimilationist model was identified between the early 1990s and the mid-2000s. Thereafter, Portugal shifted towards a multicultural model, whilst policy stability was observed in Spain. Policy variation between the two countries was mostly associated with the role of political ideas, in particular the centre-left parties’ commitment to multiculturalism. Furthermore, this investigation highlights the divergence of Portugal’s approach from the wider restrictive backlash supposedly observed in Europe, whilst Spain continues to uphold an assimilation model in the twentieth-first century.